Strategic management of zoysiagrass in the U.S. transition zone - Chhetri, Manoj (Kansas State University, 2021)
Zoysiagrasses (Zoysia spp. Willd.) are widely popular in the U.S. transition zone primarily due to lower input requirements than C₃ species, such as creeping bentgrass (Agrostis stolonifera L.), and better cold tolerance than some C₄ species, such as bermudagrass (Cynodon spp. L.C. Rich.). ‘Meyer’ zoysiagrass has long been an industry standard in the transition zone for use in golf course fairways and tees, and home lawns. The new cultivar Innovation™ offers finer leaf texture, improved shoot density, and similar cold tolerance when compared to Meyer. To expand the use of Innovation and other zoysiagrass genotypes that may be released, research on understanding water management, drought tolerance, seedhead management, large patch tolerance, and cold tolerance is needed. As such, the objectives of this dissertation were to: (1) compare Innovation zoysiagrass performance resulting from irrigation applied using the following strategies: i) a routine schedule, ii) reference evapotranspiration (ET)-based, iii) Soil moisture sensor (SMS)-based, and iv) no irrigation; (2) determine the efficacy of ethephon on Innovation zoysiagrass seedhead suppression; (3) identify and validate models that best estimate optimum application time for ethephon to suppress ‘Meyer’ zoysiagrass seedhead development; (4) evaluate the performance of ten large patch-tolerant zoysiagrass genotypes; and (5) identify new, fine-textured, cold hardy zoysiagrass genotypes. In the irrigation study, the SMS-based irrigation in Manhattan, KS saved 68% and 51% water compared to a routine schedule and ET-based irrigation, respectively. In Dallas, TX the corresponding water savings were 30% and 14%, respectively. The different soil types and the climate likely affected the performance. In Manhattan, KS ethephon applied between 20 August and 18 September were generally effective in Innovation seedhead suppression as >70% suppression was observed on three dates across two seasons. Variation between years was evident, and ethephon application based on calendar dates should be used cautiously. In a separate experiment, a multiple linear regression model, second-degree polynomial, and Gaussian function were fit to Meyer seedhead suppression following ethephon application. The seedhead suppression results were obtained from the field study conducted across four locations in the transition zone. The Gaussian model provided the best fit (adjusted determination coefficient = 0.58, root mean square error = 20.3) among the three identified models and performed best at making predictions within the peak seedhead suppression region upon verification through new independent field observations. The proposed model could be utilized as a prediction tool to effectively time ethephon for effective seedhead suppression in Meyer zoysiagrass in the transition zone. The large patch-tolerant progeny evaluation showed that experimental genotypes, DALZ 1701 and DALZ 1702 had overall better turf performance than Meyer or Innovation zoysiagrass. Another genotype, DALZ 1707 performed better than Meyer, but not as well as Innovation zoysiagrass. In a separate experiment, 20-best performing new zoysiagrass genotypes were selected from a set of 935 progeny that survived the winter from 2018 through 2020. The findings of this dissertation provide insights on innovative and sustainable approaches to zoysiagrass management and would be useful to zoysiagrass managers in the transition zone and beyond.
Keywords: Innovation zoysiagrass; Meyer zoysiagrass; Drought; Cold hardy; Large patch; Seedhead